Estimates of the Gross Domestic Product Loss due to Violence in Uganda - Nakitto, M.; Wandera, B.; Cannoodt, L.; Kiwanuka, N.; Lett, R. (Injury Prevention, 2010)
There is lack of information on economic cost of violent related injuries in Uganda. The study estimates both direct and indirect costs incurred as a result of interpersonal and self directed violent injuries. Data were collected from four hospitals and two health centres (September 2008 to November 2009) using a standardised form while medico-legal data were collected from Government chemist and Police surgeon. Estimating cost parameters were derived from a WHO Manual. Statistical analyses were done using Stata 10. Intentional injuries accounted for 20.7% of all injuries. Self-inflicted accounted for 30.3%, while interpersonal 69.7%. Violent injuries were frequent in homes; with causes: stabbing (31.1%) and poisoning (8.5%). Proportion of intentional injuries in homes was significantly higher than of unintentional injuries, 46.9% versus 23.7% (p<0.001). Direct total costs for self-directed injuries were $16 971 while per self-directed injury was $132.6. Indirect total costs for self-directed injuries were $506 443, while per self-directed injury was $3957. Direct medical costs for interpersonal injuries were $44 469, while $155 per interpersonal injury. Indirect costs for interpersonal injuries were $1 519 329, while $5312 per interpersonal injury. Direct costs due to violent injuries accounted for 0.04% of GDP while indirect costs accounted for 5.14% of GDP. Economic cost of violent injuries in Uganda is substantive and could be saved for more pressing priorities if a preventive strategy is implemented.
Keywords: Violence; Gross domestic product; Estimates